Heart transplantation in a patient with left ventricular assist device after pump thrombosis –The first case report in Serbia - Terzić, Duško; Putnik, Svetozar; Nestorović, Emilija; Bilbija, Ilija; Bukarica, Ljiljana; Jovičić, Vladimir; Rajković, Jovana; Ristić, Miljko (Vojnosanitetski pregled, 2021)
Introduction. The device thrombosis is one of the most serious complications of the left ventricle assist device implantation with a high mortality and morbidity rate. Case report. A 59-year-old male was implanted by left ventricular assist device Heart Mate II as a bridge to transplantation seventeen months before the onset of a potentially fatal complication – the thrombosis with the complete obstruction of the device. Despite the aggressive pharmacological treatment following the initial suspicion of the pump thrombosis, the patient condition got worse with the final “pump off” alarm that marked the discontinuance of the pump work as a result of the complete obstruction by the thrombus. An appropriate occurrence of an adequate donor resulted in a successful surgical treatment – the heart transplantation. Conclusion. The urgent heart transplantation by the first priority rank, or the device replacement, although technically extremely demanding procedures, are successful treatment options for these patients.